Cystathionine γ Lyase Sulfhydrates the RNA Binding Protein Human Antigen R to Preserve Endothelial Cell Function and Delay Atherogenesis - Bibli, Sofia-Iris; Hu, Jiong; Sigala, Fragiska; Wittig, Ilka; Heidler, Juliana; Zukunft, Sven; Tsilimigras, Diamantis I.; Randriamboavonjy, Voahanginirina; Wittig, Janina; Kojonazarov, Baktybek; Schürmann, Christoph; Siragusa, Mauro; et al. (Circulation (New York, N.Y.), 2019)
BACKGROUND:Hydrogen sulfide (H2S), generated by cystathionine γ lyase (CSE), is an important endogenous regulator of vascular function. The aim of the present study was to investigate the control and consequences of CSE activity in endothelial cells under physiological and proatherogenic conditions. METHODS:Endothelial cell CSE knockout mice were generated, and lung endothelial cells were studied in vitro (gene expression, protein sulfhydration, and monocyte adhesion). Mice were crossed onto the apolipoprotein E–deficient background, and atherogenesis (partial carotid artery ligation) was monitored over 21 days. CSE expression, H2S bioavailability, and amino acid profiling were also performed with human material. RESULTS:The endothelial cell–specific deletion of CSE selectively increased the expression of CD62E and elevated monocyte adherence in the absence of an inflammatory stimulus. Mechanistically, CD62E mRNA was more stable in endothelial cells from CSE-deficient mice, an effect attributed to the attenuated sulfhydration and dimerization of the RNA-binding protein human antigen R. CSE expression was upregulated in mice after partial carotid artery ligation and in atheromas from human subjects. Despite the increase in CSE protein, circulating and intraplaque H2S levels were reduced, a phenomenon that could be attributed to the serine phosphorylation (on Ser377) and inhibition of the enzyme, most likely resulting from increased interleukin-1β. Consistent with the loss of H2S, human antigen R sulfhydration was attenuated in atherosclerosis and resulted in the stabilization of human antigen R–target mRNAs, for example, CD62E and cathepsin S, both of which are linked to endothelial cell activation and atherosclerosis. The deletion of CSE from endothelial cells was associated with the accelerated development of endothelial dysfunction and atherosclerosis, effects that were reversed on treatment with a polysulfide donor. Finally, in mice and humans, plasma levels of the CSE substrate L-cystathionine negatively correlated with vascular reactivity and H2S levels, indicating its potential use as a biomarker for vascular disease. CONCLUSIONS:The constitutive S-sulfhydration of human antigen R (on Cys13) by CSE-derived H2S prevents its homodimerization and activity, which attenuates the expression of target proteins such as CD62E and cathepsin S. However, as a consequence of vascular inflammation, the beneficial actions of CSE-derived H2S are lost owing to the phosphorylation and inhibition of the enzyme.